Molecular diagnostics of cardiac allograft rejection: development pathways and future clinical prospects - D D. Velikiy; S. O. Sharapchenko; A. O. Shevchenko; O. P. Shevchenko (Вестник трансплантологии и искусственных органов, 2025)
Recent advances in molecular diagnostics have opened new avenues for integrating genetic and epigenetic bio- markers into clinical practice. Areas such as gene expression profiling, extracellular DNA quantification, and microRNA expression analysis have seen significant development in recent years. The diagnostic value of mo- lecular genetic biomarkers has been demonstrated across a range of pathological conditions. Emerging clinical data now support the use of molecular diagnostics to detect post-transplant complications in recipients of solid organ transplants. In heart transplant recipients, a comprehensive assessment that includes molecular genetics, epigenetic, and clinical parameters is essential for personalized selection of immunosuppressive therapy and for prevention of graft dysfunction and vasculopathy. This review highlights the current state of molecular diagnostics in cardiac allograft rejection and explores its potential for clinical application.